Analysis of Career Development and Employee Retention on Employee Performance with Company Technology as Moderator at PT Wira Mitra Prima (Forwarding) - Lukiyana, Lukiyana; Frianto Sinaga, Andre (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the influence of Career Development and Employee Retention on Employee Performance at PT Wira Mitra Prima, with Corporate Technology as a moderating variable. Using a sample of 100 employees, the research employed a quantitative approach with SmartPLS (Partial Least Square) and a causal design to test direct and moderating effects. The findings reveal that Career Development does not significantly affect Employee Performance, so the hypothesis is rejected. However, Employee Retention shows a significant positive effect, meaning the hypothesis is accepted. Corporate Technology also has a significant effect on Employee Performance, confirming its role as a direct driver. For moderation, Corporate Technology does not strengthen the relationship between Career Development and Employee Performance, so the hypothesis is rejected. Conversely, Corporate Technology significantly strengthens the relationship between Employee Retention and Employee Performance, meaning the hypothesis is accepted. These results highlight the importance of retention strategies and technology optimization in enhancing performance. Practical implications suggest companies should improve career development practices, strengthen retention through fair rewards and supportive environments, and maximize technology use to boost efficiency, collaboration, and productivity.